Adiponectin and Leptin at Early Pregnancy: Association to Actual Glucose Disposal and Risk for GDM—A Prospective Cohort Study - Latife Bozkurt; Christian S. Göbl; Sabina Baumgartner-Parzer; Anton Luger; Giovanni Pacini; Alexandra Kautzky-Willer (International Journal of Endocrinology, 2018)
Aim. There is scarce information on associations of adipokines, and concurrent glucose disposal during early pregnancy as performance of oral glucose tolerance is uncommon before 24th gestational week. We sought to examine associations of leptin and adiponectin to insulin sensitivity already at early pregnancy before recommended screening for GDM and to describe trajectories of adiponectin in relation to GDM status. Methods. 216 pregnant women were prospectively included at 16th (IQR: 14–18) gestational week (GW) for fasting adiponectin and leptin with subsequent OGTT testing for evaluation of insulin sensitivity and β-cell function. Follow-ups of adiponectin were performed at further four visits until 8–12 weeks after delivery. Results. In early pregnancy, differences in adiponectin and leptin were significant between GDM women (n=82) and controls (n=134), whereby those with early GDM (<21st week, n=49) showed more distinguishing levels (adiponectin: 8.5 ± 3.8 versus 10.4 ± 4.4 μg/ml, p=0.004; leptin 93.4 ± 38.5 versus 78.0 ± 39.2 μg/ml, p=0.005). Both adipokines were significantly associated with insulin sensitivity and β-cell function. Their attribution for GDM prediction was moderate to fair and more enhanced in early GDM. Trajectories of adiponectin remained constantly lower in GDM women, whereas dynamics in controls showed initially increased concentrations with decreasing tendency until 3rd trimester. After delivery, low adiponectin was associated with glucose dysregulation. Conclusion. Associations of adiponectin and leptin with features of deteriorated glucose metabolism at early gestation may be indicative for the endocrine involvement of adipose tissue in the manifestation of GDM and thus predictive for later impairments in metabolic flexibility in women at risk.